The interplay of motifs and instruments in RADWIMPS’ “Sparkle”: A compositional analysis - Danny Ceri; Athariq Dwi Rizky Pratama (Universitas Pendidikan Indonesia, 2023)
The relationship between film and music is a deep and intricate phenomenon that significantly shapes the viewer's experience by blending visuals and audio to create a beautifully captivating ambiance. This synthesis is especially crucial in genres such as drama, supernatural, and fantasy when music serves as a channel to the imaginary worlds depicted on television. The 2016 Japanese fantasy animation film *Kimi no Na wa* (Your Name) demonstrates the connection between well-crafted music and a film's narrative and emotional depth. It showcases character design by Masayoshi Tanaka and a remarkable score by the Japanese rock band RADWIMPS. The tale centers around a schoolgirl hailing from rural Japan and a student residing in Tokyo who inexplicably swap bodies, creating the backdrop for a very emotional story. This research underscores the importance of the soundtrack, namely RADWIMPS's utilization of piano, in evoking emotional and imaginative reactions. The study highlights the intricate influence of music in films, impacting psychological, visual, emotional, and imaginative processes. Music enhances the cinematic experience by setting the mood, intensifying feelings, and providing a captivating background, transporting the viewer to different worlds. This study aims to explore the optimal utilization of music in fantasy and supernatural films to enhance storytelling and engage spectators in response to the growing output of such films. This study employs a qualitative research approach to examine the recurring utilization of piano motifs in the music of *Kimi no Na Wa* and its influence on the cinematic experience. The findings illustrate that particular musical components substantially impact how the audience perceives and emotionally responds, offering vital insights for filmmakers and researchers. This study emphasizes the multifaceted function of music in improving storytelling and its significant influence on viewers' emotional and psychological involvement